Elements of Factual Narrative Text at Sosok Section in Kompas Newspaper 2018 - Wida Hernawati (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2019)
This article discusses abaout the elements of factual narrative text at Sosok section in Kompas newspaper 2018. The results of the study of factual narrative text in sosok section is expected to be used as a source of teaching material in writing factual narrative text at school. The subject of this research is sosok section  in Kompas daily newspaper 2018. The objects of this research are intrinsic elements of narrative text including background, series of events and characterizations in the sosok section. This study aims to describe background, series of events and characterizations and the results will be used to compile teaching materials in learning to write inspirational story. The method used was a qualitative research method. To collect data, the technique used was document study. The data were analyzed qualitatively. Based on the results of analysis, the results show that social background of the figure, educational background of the figure, and the natural environment in the rubric were very diverse. Social background of the figures in this rubric are from academia, artists, and common people. Their educational backgrounds also vary, from a professor to a high school graduate. The age of figures also vary, from 22 to 70 years old. Even the genders are various. The natural environment in which the figures are located is various, starting from urban areas, rural areas and even inland and disaster-prone areas. The series of events in the sosok section are interwoven chronologically and based on cause-effect.Keywords : factual narrative, sosok section.